RANG AND DALE'S Pharmacology - Rang, H. P.; Dale, M. Maureen; Ritter, James; Flower, R.J; Henderson, G. (Elsevier/Churchill Livingstone, 2012)
This edition sets out a clear route through pharmacology for the reader, from a molecular understanding of receptors and drug actions to the clinical use of the most important groups of drugs. It contains everything students need to know about pharmacology in their early years.